Macrolepiota procera (Scop.) Singer (Agaricomycetes) - a new generic record of edible mushroom for Nagaland, Northeast India (Asian Journal of Agriculture, 2017)
Abstract. Kumar R, Pandey S, Rishi RR, Giri K. 2017. Macrolepiota procera (Scop.) Singer (Agaricomycetes) - a new generic record of edible mushroom for Nagaland, Northeast India. Asian J Agric 1: 6-8. In August 2013, an interesting mushroom was collected from the Puliebzie forest range in Kohima District of Nagaland state of India. The mushroom was identified as Macrolepiota procera (Scop.) Singer based on the macroscopic and microscopic characters.
Keywords: Macrolepiota procera; mushroom; Nagaland; new generic record